The Role of IL-15 Deficiency in the Pathogenesis of Virus-Induced Asthma Exacerbations - Laza-Stanca, Vasile (Public Library of Science, 2011)
Rhinovirus infections are the major cause of asthma exacerbations. We hypothesised that IL-15, a cytokine implicated in innate and acquired antiviral immunity, may be deficient in asthma and important in the pathogenesis of asthma exacerbations. We investigated regulation of IL-15 induction by rhinovirus in human macrophages in vitro, IL-15 levels in bronchoalveolar lavage (BAL) fluid and IL-15 induction by rhinovirus in BAL macrophages from asthmatic and control subjects, and related these to outcomes of infection in vivo. Rhinovirus induced IL-15 in macrophages was replication-, NF-κB- and α/β interferon-dependent. BAL macrophage IL-15 induction by rhinovirus was impaired in asthmatics and inversely related to lower respiratory symptom severity during experimental rhinovirus infection. IL-15 levels in BAL fluid were also decreased in asthmatics and inversely related with airway hyperresponsiveness and with virus load during in vivo rhinovirus infection. Deficient IL-15 production in asthma may be important in the pathogenesis of asthma exacerbations.